ADDRESSING CHALLENGES IN TEACHING ENGLISH IN CENTRAL ASIAN COUNTRIES: A SCHOLARLY EXAMINATION - Shoimqulova, Nigina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article explores the complexities and challenges faced by educators in teaching English in Central Asian countries. It examines the linguistic and cultural hurdles, particularly focusing on grammar differences, and offers viable solutions to enhance the efficacy of English language instruction. Through a scholarly lens, this study provides insights into the nuances of English language education in the context of Central Asia.